Management Effectiveness of Southeast Aru Islands Marine Conservation Area - Dangeubun, Fernando Dayandri Willem; Wiryawan, Budy; Mustaruddin, .; Purbayanto, Ari (Jurnal Manajemen Hutan Tropika, 2013)
Southeast Aru Islands Marine Conservation Area (SE Aru MCA) has been existed for nearly 21 years, a period that long enough for a timely evaluation about how far improvement of management has been made in the area in question, i.e. whether management has improved situation of local communities and marine resources availability in the area. This study, therefore, aims at assessing management effectiveness and impacts of SE Aru MCA. Results suggest that the MCA, which was originally established as a marine nature reserve (Cagar Alam Laut, CAL) in 1991 and changed status into marine sanctuary in 2009, has not yet produced the expected positive impacts. Assessment using available tools indicated that the management level of SE Aru MCA is at level 1, with percentage of 34.12%, meaning it is still at initiation stage and less effective in terms of management outcomes. Index of conservation area effectiveness with a value of 0.387 shows that the overall conservation area in the 3 categories mentioned above is less effective, therefore conservation effect has not been able to solve area problems. It is concluded that, after more than 20 years exists in the area, few benefits have been produced by SE Aru MCA for local people associated with it and biological resources in it.